Characterization and Structural Insights of the Reaction Products by Direct Leaching of the Noble Metals Au, Pd and Cu with N,N′-Dimethyl-piperazine-2,3-dithione/I2 Mixtures - Angela Serpe; Luca Pilia; Davide Balestri; Luciano Marchiò; Paola Deplano (Molecules, 2021)
In the context of new efficient and safe leaching agents for noble metals, this paper describes the capability of the Me2pipdt/I2 mixture (where Me2pipdt = N,N′-dimethyl-piperazine-2,3-dithione) in organic solutions to quantitatively dissolve Au, Pd, and Cu metal powders in mild conditions (room temperature and pressure) and short times (within 1 h in the reported conditions). A focus on the structural insights of the obtained coordination compounds is shown, namely [AuI2(Me2pipdt)]I3 (1), [Pd(Me2pipdt)2]I2 (2a) and [Cu(Me2pipdt)2]I3 (3), where the metals are found, respectively, in 3+, 2+ and 1+ oxidation states, and of [Cu(Me2pipdt)2]BF4 (4) and [Cu(Me2dazdt)2]I3 (5) (Me2dazdt = N,N′-dimethyl-perhydrodizepine-2,3-dithione) compared with 3. Au(III) and Pd(II) (d8 configuration) form square–planar complexes, whereas Cu(I) (d10) forms tetrahedral complexes. Density functional theory calculations performed on the cationic species of 1–5 help to highlight the nature of the bonding in the different complexes. Finally, the valorization of the noble metals-rich leachates is assessed. Specifically, gold metal is quantitatively recovered from the solution besides the ligands, showing the potential of these systems to promote metal recycling processes.